2022
DOI: 10.1002/cctc.202200981
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Power for Electrocatalytic Generation of Syngas: Tuning the Syngas Ratio by Manipulating the Active Sites and System Design

Abstract: Achieving decarbonization through zero net CO2 emissions requires commercially viable application of waste CO2, throughout the transition to renewable and low‐carbon energy sources. A promising approach is the electrochemical carbon dioxide reduction reaction (CO2RR), which when powered with renewable electricity sources, provides a pathway for the conversion of intermittent renewable energy and waste CO2 into value‐added chemicals and fuels. However, as CO2RR is accompanied by the competing hydrogen evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 215 publications
0
2
0
Order By: Relevance
“…According to different techno-economic assessments (TEAs), electrochemical production of CO can already be profitable, if the technology is available at scale. ,, Furthermore, for applications where a steady supply of syngas is not needed, the electrochemical reduction of CO 2 provides a unique opportunity to convert intermittent but abundant renewable energy source into chemical fuels . What is equally important, different life cycle assessment (LCA) studies confirmed that such electrochemical routes can have a significant reduction in CO 2 footprint, compared to the traditional methods. , Meeting these three conditions together (i.e., economic viability, CO 2 footprint decrease, and large market size) predicts a great promise for electrochemical CO 2 -to-CO conversion.…”
Section: Electrochemical Syngas Generationmentioning
confidence: 99%
“…According to different techno-economic assessments (TEAs), electrochemical production of CO can already be profitable, if the technology is available at scale. ,, Furthermore, for applications where a steady supply of syngas is not needed, the electrochemical reduction of CO 2 provides a unique opportunity to convert intermittent but abundant renewable energy source into chemical fuels . What is equally important, different life cycle assessment (LCA) studies confirmed that such electrochemical routes can have a significant reduction in CO 2 footprint, compared to the traditional methods. , Meeting these three conditions together (i.e., economic viability, CO 2 footprint decrease, and large market size) predicts a great promise for electrochemical CO 2 -to-CO conversion.…”
Section: Electrochemical Syngas Generationmentioning
confidence: 99%
“…Alkaline flow cells and neutral membrane electrode assembly (MEA) are widely used as CO 2 electrolyzers in the literature [13][14][15]. They have the advantages of compact structure, high current density, low cell voltage, etc.…”
Section: Introductionmentioning
confidence: 99%